2007
DOI: 10.1261/rna.654407
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of a Pop6/Pop7 heterodimer to the P3 stem of the yeast RNase MRP and RNase P RNAs

Abstract: Pop6 and Pop7 are protein subunits of Saccharomyces cerevisiae RNase MRP and RNase P. Here we show that bacterially expressed Pop6 and Pop7 form a soluble heterodimer that binds the RNA components of both RNase MRP and RNase P. Footprint analysis of the interaction between the Pop6/7 heterodimer and the RNase MRP RNA, combined with gel mobility assays, demonstrates that the Pop6/7 complex binds to a conserved region of the P3 domain. Binding of these proteins to the MRP RNA leads to local rearrangement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
83
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 30 publications
16
83
1
Order By: Relevance
“…This value is comparable to the one obtained for another heterodimer known to bind RNase MRP RNA, Pop6/Pop7 (K d = 110 6 40 nM) (Perederina et al 2007). It was suggested that the presence of proteins already bound to RNA, or a simultaneous cooperative binding of several protein subcomplexes, may improve Pop6/Pop7 binding during RNase MRP assembly (Perederina et al 2007); it is likely that this is the case for the Pop5/Rpp1 heterodimer as well.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This value is comparable to the one obtained for another heterodimer known to bind RNase MRP RNA, Pop6/Pop7 (K d = 110 6 40 nM) (Perederina et al 2007). It was suggested that the presence of proteins already bound to RNA, or a simultaneous cooperative binding of several protein subcomplexes, may improve Pop6/Pop7 binding during RNase MRP assembly (Perederina et al 2007); it is likely that this is the case for the Pop5/Rpp1 heterodimer as well.…”
Section: Resultssupporting
confidence: 77%
“…We did not observe the binding of the Pop5/Rpp1 heterodimer to control yeast tRNA or to 140-nt-long (mostly single-stranded) RNA containing a fragment of the internal transcribed spacer 1 (ITS1), a known substrate for RNase MRP (Esakova et al 2011, and references therein; data not shown). Our attempts to perform similar experiments using yeast RNase P RNA did not yield interpretable results, apparently due to misfolding of RNA; the same problem was encountered previously (Perederina et al 2007). …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This region serves as the binding site for proteins (conflicting data suggest that this is either Pop1 or a Pop6/7 heterodimer) that may recruit the other essential proteins to nucleate the assembly of the holoenzyme. 38,39 Other RNA structures found in Archaea and Bacteria (P13, P14 and L15) are missing all together in nuclear RNase P RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…These latter RNAs are the central and essential moieties of the highly conserved yeast RNaseMRP and RNaseP RNP enzymes . Further work showed that the Tlc1 P3-like domain associates with the Pop1/Pop6/Pop7 proteins; most likely via a similar architecture as determined for the Nme1 P3 domain in the yeast RNaseMRP (Perederina et al 2007;Perederina et al 2010;Fagerlund et al 2015;Lemieux et al 2016). Previous results also showed that a deletion of the Tlc1 P3-like domain caused a complete loss of Est1 from Cold Spring Harbor Laboratory Press on April 1, 2019 -Published by rnajournal.cshlp.org Downloaded from the telomerase RNP and Est2 binding was reduced (Lemieux et al 2016).…”
mentioning
confidence: 85%